2021
DOI: 10.1016/j.scitotenv.2020.141987
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of artificial waterbodies to biodiversity: A glass half empty or half full?

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Even though spring ecosystems and their biodiversity are threatened worldwide, those from Mediterranean‐type regions suffer the consequences of global change more strongly because their intrinsic water limitation exacerbates other potential problems, such as eutrophication (Fernández‐Martínez et al., 2020; Martín et al., 2024). Furthermore, it is in these regions where spring ecosystems play an important role in sustaining biodiversity because they represent isolated habitats with permanent water availability surrounded by habitats where water is not typically available (Fernández‐Martínez, Berloso, et al., 2019; Zamora‐Marín, Ilg, et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Even though spring ecosystems and their biodiversity are threatened worldwide, those from Mediterranean‐type regions suffer the consequences of global change more strongly because their intrinsic water limitation exacerbates other potential problems, such as eutrophication (Fernández‐Martínez et al., 2020; Martín et al., 2024). Furthermore, it is in these regions where spring ecosystems play an important role in sustaining biodiversity because they represent isolated habitats with permanent water availability surrounded by habitats where water is not typically available (Fernández‐Martínez, Berloso, et al., 2019; Zamora‐Marín, Ilg, et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Small ponds are in general more biodiverse than larger lakes possibly due to the lack of large fish (Scheffer et al 2006). Although ponds in the urban environment are degraded compared to ponds in nature areas (Biggs et al 2005, Zamora-Marín et al 2021, they still significantly contribute to the urban's regional biodiversity (Indermuehle et al 2004, Davies et al 2008, Loram et al 2011. In their study, Hill et al (2019) indicated that local environmental conditions are the primary drivers of macroinvertebrate biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…Freshwater blue spaces (rivers, streams, shallow lakes, ponds) represent key environments in the urban landscape as they are beneficial for the citizens' health and well‐being (McDougall et al, 2022; Miró et al, 2018; Mitroi et al, 2022), and have high ecological value showing a positive impact on biodiversity (Hassall, 2014; Krivtsov et al, 2022; Oertli & Parris, 2019; Zamora‐Marín et al, 2021). In particular, urban ponds are often numerous and can act as refuges for threatened species, stepping stones for the migration of different organisms (Blicharska & Johansson, 2016; Hassall et al, 2016) allowing the movement of individuals and genes (Miró et al, 2018).…”
Section: Introductionmentioning
confidence: 99%